Bioglycerol (C3) upgrading to 2,3-butanediol (C4) by cell-free extracts of Enterobacter aerogenes NCIM 2695 - Parate, Roopa; Borgave, Mrunal; Dharne, Mahesh; Rode, Chandrashekhar (Journal of Chemical Technology and Biotechnology, 2021)
BACKGROUND Production of biobased chemicals from renewable resources is a green starring approach that serves as a substitute to petroleum derivatives. Bioglycerol, with its growing production as a co-product of biodiesel, is an attractive low-cost feedstock for the synthesis of platform chemicals by microbial fermentation. 2,3-butanediol (2,3-BDO) is amongst the top biorefinery platform chemicals that can be produced by glycerol fermentation. RESULTS The `Circular Economy' concept is demonstrated by converting the by-product bioglycerol using a cell-free extract of Enterobacter aerogenes NCIM 2695 (National Collection of Industrial Microorganisms, NCIM), yielding 22 g L-1 2,3-BDO, in 96 h, 98% atom economy and 0.4 g/g E factor. The cell-free bioglycerol conversion to 2,3-BDO was proved using a modified procedure for determining glycerol dehydrogenase enzyme assay by protein analysis and it was also shown to be cell-bounded. CONCLUSION Our study offers an effective utilization of the leftover material (i.e. cell-free extract) that biocatalysed C3 to C4 diol, which adds value to the overall economics of the process using only crude glycerol (C3) itself as a fermentative medium.
Keywords: 2; 3-Butanediol; atom economy; circular economy; E factor; Glycerol; glycerol dehydrogenase

Atom-economical and scalable asymmetric synthesis of daridorexant key starting material (S)-2-methylproline via the memory of chirality - Bhatt, Gaurang J.; Kumar, Shubham; Mhaske, Santosh B. (Organic Process Research & Development, 2025)
alpha-Methylproline is a key starting material (KSM) for important drugs, such as Daridorexant, Veliparib, Trofinetide, Enlicitide chloride, and Usnoflast. A practical and scalable asymmetric synthesis of (S)-2-methylproline and its derivatives has been disclosed here using a diketopiperazine intermediate-based strategy that leverages the memory of chirality. Commencing from an inexpensive starting material, l-proline, it proceeds through dimerization and alkylation, followed by hydrolysis under mild conditions, avoiding column chromatography to furnish enantiomerically pure (S)-2-methylproline.HCl, which was also converted to (S)-Boc-2-methylproline and (S)-2-methylproline methyl ester.HCl. In contrast to prior multistep approaches, which rely on expensive chiral auxiliaries and hazardous reagents, this concise three-step route offers operational simplicity, scalability, and superior stereochemical control, making it an attractive method for the synthesis of proline-derived building blocks for peptidomimetics and pharmaceutical applications.
Keywords: alpha-methylproline; atom economy; memoryof chirality; Stereoselective